Identification of energy and carbon efficient cropping system for ecological sustainability of rice fallow. (August 2020) - Lal, B.; Gautam, Priyanka; Panda, B.B.; Tripathi, R.; Shahid, M.; Bihari, P.; Guru, P.K.; Singh, Teekam; Meena, R.L.; Nayak, A.K.
Graphical abstract: Highlights: Impact of diversification of rice establishment on energy and carbon budgeting was evaluated. Crop diversification enhanced system productivity from 4 t ha −1 to 6–6.5 t ha −1 . Dry-direct seeded rice reduced 18.4% energy consumption and 10% carbon footprints (CFs). Diversification helps in reducing carbon footprints up to 315% as compared to monoculture. Designing a system with low energy and CFs is necessity for sustainability of rice fallow. Abstract: Reducing energy and carbon inputs and enhancing their use efficiencies are essential to ensure energy security and long-term sustainability of rice production especially under fallow. Hence identification of suitable cropping systems for rice-fallow can be a powerful strategy to mitigate the climate change through reduced energy consumption and carbon footprints. Therefore, the study was conducted to quantify the energy budgeting, carbon footprint and productivity of different establishment methods, cultivars and dry season crops that are suited for rice fallow lands. Diversification of rice fallow resulted in the additional equivalent yield of 2 t ha −1, and productivity of cropping system enhanced from 4 t ha −1 to 6–6.5 t ha −1 . Dry-direct seeded rice (DSR) reduced 18.4% energy consumption over transplanted rice (TPR), in which major energy-saving was in diesel (160%), machinery and labor (66%) making dry-DSR more energy profitable with a minor yield penalty. The carbon footprints were 3.7 and 10.3% higher in TPR as compared to wet-DSR and dry-DSR, respectively. Though diversification of rice fallow added to system productivity, both energy consumption and carbon foot prints were also lower for dry season crops viz., toria, green gram and black gram. Therefore, their inclusion in cropping systems is not only productive and profitable but environmentally sustainable too.